Dendeicultura e capitalismo: o processo de trabalho assalariado na monocultura do dendê (Revista de História Regional, 2025)
The oil palm economies in Indonesia and Brazil were supported by neo-developmentalist state initiatives that sought to specialize these regions in neo-extractive activities, suppliers of primary consumer goods. In this sense, this article seeks to analyze wage labor in oil palm monoculture in Brazil in light of reflections made in studies on the subject in Indonesia (the world's largest oil palm producer). For this purpose, a qualitative and quantitative research was carried out among rural wage workers in Igarapé-Açu/PA, combined with literature that provides evidence on wage labor in Indonesia. The information points to a labor process that is harmful to the workers themselves, with: work accidents, health-related problems, exposure to chemicals, and extended working hours.
Keywords: agricultural labor; rural wage earners; neo-extractivism; workers.